COVID-19: A brain virus? COVID-19 and neurological manifestations: a systematic review - Muhammad Mohsin Khan; Noman shah; Gianluca Scalia; Eberval Gadelha Figueiredo; Giuseppe Emmanuele Umana; Matias Baldoncini; Luis A. B. Borba; Vishal Chavda; Carlos Castillo Rangel; Mohsin Fayaz; Bipin Chaurasia (Egyptian Journal of Neurosurgery)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for Corona Virus Disease-19 (COVID-19), initially identified in Wuhan, China, has been primarily recognized as a respiratory pathogen. However, evidence has emerged suggesting its impact on various organ systems, including the central nervous system. This systematic review aims to comprehensively investigate and analyze the neurological manifestations of COVID-19, shedding light on its potential as a brain-invading virus. Methods A systematic literature search was conducted across multiple databases, including Google Scholar, PubMed, Cureus, and the World Health Organization’s database. Studies employing case–control methods, population-based cohort studies, or human clinical trials were prioritized for data extraction. The Joanna Briggs Institute tool was employed for quality assessment. Results Neurological manifestations in COVID-19 patients vary widely, ranging from headache, dizziness, and myalgias to severe complications such as stroke, seizures, and encephalopathy. Encephalopathy emerged as a common complication, affecting up to 40% of patients. Stroke incidence ranged from 1 to 6%, and seizures were reported in 0.6% to 13.5% of cases. Peripheral nerve disorders and Guillain-Barré Syndrome were also documented. Mechanisms of neurological injury include direct viral invasion, immune-mediated inflammation, and hypoxia. Conclusions COVID-19 exhibits a range of neurological manifestations beyond its respiratory impact. Encephalopathy, stroke, seizures, and peripheral nerve disorders are among the severe complications reported. The mechanisms underlying these neurological effects remain complex and multifaceted. Recognition of these manifestations is crucial for timely and appropriate management.